O papel do Fundo Constitucional de Financiamento do Nordeste na diminuição das desigualdades inter e intrarregionais : o caso de Sergipe e Alagoas - Silva, Eliane Correia dos Santos (2014)
The purpose of this dissertation is to analyze the role played by the Constitutional Fund for Financing the Northeast (FNE) on the economies of Sergipe and Alagoas in the period of 1989-2010. Part is the statement that this fund, established in 1988 Constitution, with the aim of contributing for the reduction of regional disparities in Brazil, is an important source of income transferred to the Northeast. The main objective is to analyze the transfers of FNE according to spatial allocation, sectorial distribution and by size of enterprise, with an emphasis in the states of Sergipe and Alagoas, in order to understand if they are reaching the goal set in its institution. The sources used in the study were data available from the Ministry of National Integration (MI), the Brazilian Institute of Geography and Statistics (IBGE) and the Bank of Northeast Brazil (BNB). Through the analysis, it was found that the applications of FNE are increasing, and there have been advances in the directions of resources, but there are imperfections in the allocation of these and is needed improvements in the spatial distribution, by size of the beneficiary and in the productive sectors that are more strategic for the development of the region.